2021
DOI: 10.11591/ijere.v10i3.21573
|View full text |Cite
|
Sign up to set email alerts
|

Student’s general attitude in gender-inclusive language

Abstract: Centered on studies on language and gender, this study generally aimed to assess the students’ general attitude towards Gender-Inclusive It likewise determined difference on attitude when grouped according to sex. The study utilized quantitative research design. Survey questionnaire using the IASNL was the instrument used which assesses beliefs, recognition of sexist language and willingness to use gender-inclusive language. Respondents utilized were randomly selected students of the College of Teacher Educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Research found that websites using gender-inclusive language and imagery resulted in improved user satisfaction for all genders (Remigio & Talosa, 2021).…”
Section: Successmentioning
confidence: 99%
“…Research found that websites using gender-inclusive language and imagery resulted in improved user satisfaction for all genders (Remigio & Talosa, 2021).…”
Section: Successmentioning
confidence: 99%